2017
DOI: 10.4018/ijiscram.2017070104
|View full text |Cite
|
Sign up to set email alerts
|

Serious Game Design for Flooding Triggered by Extreme Weather

Abstract: Managing crises with limited resources through a serious game is deemed as one of the ways of training and can be regarded as an alternative to a table-top exercise. This article presents the so-called “Operasjon Tyrsdal” serious game, inspired by a real case of extreme weather that hit the west coast of Norway. This reference case is used to add realism to the game. The game is designed for a single player, while the mechanics are framed in such a way that the player will have limited resources, and elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Tanes and Cho (2013) conducted a user experience survey to statistically prove how "Beat the Quake" gamified application changed the playing community behaviour positively in preparing themselves for upcoming disasters. Besides, ), Mani et al (2016), and Radianti et al (2017 revealed the effectiveness of using gamified applications in motivating players to gain disaster awareness by conducting user experience surveys before and after playing the applications. Findings of these studies disclosed that the more people play these games, the more they get motivated.…”
Section: Continuous Outputs and Behavioural Changementioning
confidence: 99%
“…Tanes and Cho (2013) conducted a user experience survey to statistically prove how "Beat the Quake" gamified application changed the playing community behaviour positively in preparing themselves for upcoming disasters. Besides, ), Mani et al (2016), and Radianti et al (2017 revealed the effectiveness of using gamified applications in motivating players to gain disaster awareness by conducting user experience surveys before and after playing the applications. Findings of these studies disclosed that the more people play these games, the more they get motivated.…”
Section: Continuous Outputs and Behavioural Changementioning
confidence: 99%